CHINA’S INFORMATION TECHNOLOGY MODERNIZATION: FROM DOMESTIC REFORM TO GLOBAL INFLUENCE - Zhubaniyazova, У.Б. (Journal of Oriental Studies, 2025)
The article examines the process of China’s modernization in the field of information technology, starting with internal reforms and ending with the country’s global influence in the digital sphere. IT ananological superpower, and identifies key factors that have allowed China to take a leading position on the global stage. The novelty of the article lies in a comprehensive approach to analyzing the relationship between China’s internal reforms and its global influence in the field of information technology. Special attention is paid to comparing the Chinese modernization model with other global centers of technological progress, as well as assessing the strategies and challenges faced by China in the context of global competition. Objective: To characterize the main reforms carried out in China since the early 2000s in the field of information technology. Identify what changes have occurred in government policy, education, and infrastructure that have contributed to the development of the sector. The article assesses the role of the state in the development of innovative technologies and creating conditions for the growth of technology companies, analyzes how Chinese companies such as Huawei, Tencent, Alibaba and Baidu are expanding their influence in the global information technology market and what strategic steps China is taking to ensure technological leadership in the world. The purpose of the article is to study the evolution of the Chinese information economy, to analyze the role of government strategies such as the Digital China Initiative and their impact on global digital transformation. It also examines the challenges and prospects that China faces in the face of growing international competition. The research uses methods of system analysis, comparative analysis and historical and economic analysis. Secondary sources were used to collect the data, including statistical reports, research from Chinese and international think tanks, as well as research from key Chinese technology companies. Results: China’s modernization in the field of information technology has led to the creation of a powerful digital infrastructure and an increase in global influence. Internal reforms in the field of Internet access, mobile technologies and artificial intelligence have become the basis for the country’s transformation into a technological leader. China’s influence on the international information technology market is increasing through companies such as Huawei and Alibaba, which is confirmed by their expansion into the global market and their influence on the development of 5G, artificial intelligence and blockchain technologies. The article also shows how China’s political and economic features, including government interference in innovation, affect its strategic position in the global market. Keywords: information technology (IT), digital transformation, artificial intelligence, startup ecosystem, Chinese innovations, internal reforms, China’s global influence.